A STUDY OF TEACHER TALK AND STUDENT TALK IN VERBAL CLASSROOM INTERACTION TO DEVELOP SPEAKING SKILL FOR YOUNG LEARNERS - Ami Fatimah Mulyati (Journal of English and Education, 2013)
This study aims at investigating the realization of verbal classroom interaction especially teacher talk and students talk that occurred during teaching speaking. The data were taken from one private school in Bandung in the form of observations and interviews. The data then were analyzed by the framework adapted from Flanders’ Interaction Analysis Categories (1970) and FACCT from Kumpulainen and Wray (2002). The findings indicated that the teacher acted as the most dominant interlocutor during speaking activity. Besides, it also showed that the teacher’s roles during interaction as director, manager, and facilitator. The study recommends the teacher to support students to have more opportunity to speak during the lesson. Finally, this study suggests further study to conduct similar research which covers different skills. Keywords: Classroom interaction, teacher talk, student talk, young learners